Meeting the demand for livestock feeds in developing countries - Fernández Rivera, S.; Pezo, Danilo A.; Devendra, C. (International Livestock Research Institute, 2002)
The livestock revolution is occurring but it is being preceded by the feed revolution because of the substantial mount of feed required to supply by the increased animal population. However, the opportunities to meet the demand for feed depend on the existing production systems. This paper looks into ILRI's current research in livestock feeds and nutrition; feed production and utilisation projects; opportunities for research in livestock feeds and nutrition in South-East Asia with special reference to livestock production systems; feed resources in smallholder farming systems; and research and development opportunities.